Desgaste de materiais restauradores para CAD/CAM - Tumelero, Flávia (2019)
The wear of restorative materials during function can lead to increased surface roughness, accumulating biofilm and altering the occlusal anatomy and contact points. These factors can lead to reduced restoration longevity and represent a concern for the clinical performance of new restorative materials for CAD/CAM. This study aimed to evaluate the wear resistance of two restorative materials for CAD/CAM: a nanoceramic resin (Lava Ultimate, LU) and a glass-ceramic reinforced with leucite (IPS Empress Esthetic, VL). CAD/CAM blocks of the materials were sliced with a metallographic cutter, polished and cemented with resin cement onto a dentine-like substrate. The specimens (CP) of each material were divided into three groups, according to the number of cycles used in the wear test (n=4): 100,000, 250,000 and 500,000. The CPs were positioned at a 30º inclination and a load of 49 N was applied to the surface with a frequency of 2 Hz. The test was carried out in distilled water at 37º C. After the test, images of the surface of the PCs were obtained to measure the area of wear (mm2). The CPs were also scanned with a laser scanner and the maximum wear depth (mm) was measured with specific software. The length of the wear facet was similar for VL and LU, however, the width of the wear facet was greater in VL. This caused the largest wear area in VL, while LU lost more material in depth.